Educação para sustentabilidade e a ação conjunta de tecer redes de transição no território - Fortes, Adriana Benetti (2023)
Included in the Education Program: Curriculum, in the research line on Public Policies and Educational and Curriculum Reforms, this research originates from the urgency presented by the environmental challenges currently facing our societies. Based upon the theme of Education for Sustainability, the dissertation is designed to integrate knowledge based on transdisciplinary and complexity. The weaving of the local sustainability network in the territory of Vila Mariana, São Paulo, Brazil, supported by the Transition Towns movement, is analyzed through participatory action research. To delve into the theme, we investigated some aspects of the socio-climatic crisis, the motto of the Transition Towns movement, and also the paradigms of the human beings relationship with nature, verifying the evolution of the concept of the land as a being with rights whilst confronted with indigenous cosmovision to broaden this understanding. The context is presented by reading the contemporary world in the dimension amplified by the covid-19 pandemics. Current conceptions of ecological education are questioned, which are placed in dialogue with a reflection on education, curriculum, and sustainability. As part of the research methodology, a semi-structured questionnaire was prepared and proposed to the participants of the analyzed process. The study is presented and divided into sections that refer to the elements of nature, with brief poetic-narrative frameworks